PENERAPAN MODEL KANO PADA PERANCANGAN KUALITAS PELAYANAN - Anshory, Heffy Hasim; Hapsari, Raditha Dwi Vata (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to identify important attributes of barbershop services according to customer perspectives. Data was collected through Google Forms from customers in Sragen Regency. Validity and reliability were assessed using JASP, and analysis employed the Kano model. Findings revealed three customer need categories: one-dimensional, attractiveness, and indifference. One-dimensional needs include easy access, cleanliness, and well-groomed staff. Attractiveness needs are not expected but enhance satisfaction, such as a comfortable waiting area and complete tools. Indifference needs are negligible and do not affect satisfaction. To improve satisfaction, barbershops should focus on one-dimensional and attractiveness needs, fulfilling indifference needs upon request. Understanding and meeting customer needs effectively enhance satisfaction and profitability. Recommendations include prioritizing one-dimensional and attractiveness needs, responding to indifference needs when requested, improving communication, and continuous evaluation.